The earth book. - Jennings, Gary. (Philadelphia, Lippincott, 1974)
Examines the many different kinds of pollution to which man is subjecting the earth and outlines some steps the reader can take to deal with this problem.
Keywords: Ecology -- Juvenile literature; Pollution -- Juvenile literature; Ecology; Pollution